Evolution of microstructure and nanohardness of SiC fiber-reinforced SiC matrix composites under Au ion irradiation. Issue 6 (15th April 2020) - Ye, Chao; Xue, Jiaxiang; Liu, Tong; Shu, Rui; Yan, Yan; Liao, Yehong; Ren, Qisen; Ran, Guang; Sun, Kai; Jiang, Li; Xiu, Pengyuan; Wang, Lumin
Abstract: Evolution of microstructure and nanohardness of a new type of SiCf /SiC composite under a 6 MeV Au ion irradiation up to 90 displacements per atom at 400 °C was studied. Scanning transmission electron microscopy reveals that the irradiation has induced enrichment of carbon at the grain boundaries in the fibers. This is attributed to the accumulation of C interstitials generated by the irradiation. The disappearance of {200} diffraction ring of 3C–SiC indicates that a phase transition from 3C–SiC to Si has occurred during irradiation. In addition, the hardness of SiC fiber increased after irradiation, which is due to the pinning effect caused by irradiation-induced defects. The pyrolytic-carbon interphase that contains Si-rich nano-grains in the composite has the highest irradiation tolerance as it maintained its basic morphology and graphitic nature after a radiation damage dose up to 90 dpa. Twins are the main internal defects in the SiC matrix of the SiCf /SiC composite, which grew up and resulted in the decrease of the number of twinning boundaries under irradiation. No significant microstructure change has been observed in the SiC matrix except a limited number of dislocation loops at the peak irradiation damage region. The entire matrix still maintained its hardness after irradiation.